Knowledge of Dental Residents at Shahid Beheshti Dental School about COVID-19 - Jafari, Soudeh; Bigom Taheri, Jamileh; Raeisi, Negar; Hasani, Ahmad (Journal of Dental School, 2022)
Objectives After the onset of coronavirus disease-2019 (COVID-19) pandemic in 2019, it turned out to be one of the most important issues in public health, and the healthcare community must have adequate knowledge about it; therefore, this study was conducted to evaluate the knowledge level of dental residents at Shahid Beheshti Dental School about COVID-19. Methods The knowledge level of 104 dental residents at Shahid Beheshti Dental School about COVID-19 was evaluated with a standardized questionnaire that was developed, and its reliability and validity were confirmed. The questionnaire had 4 parts of (I) virology, basic information, and epidemiology, (II) clinical and oral manifestations, (III) prevention of virus transmission and vaccination, and (IV) diagnosis and treatment. The questionnaires were administered in both printed and online forms. Results The overall response rate was 72%. The mean number of correctly answered questions was 7.2 ± 2.6 out of 14. Correct answers were 44.5% in virology, basic information, and epidemiology, 49.2% in clinical and oral manifestations, 48,5% in prevention of virus and vaccination, and 69% in diagnosis and treatment. The knowledge level of dental residents was weak in 12%, average in 52%, and good in 36%. Conclusion The majority of dental residents had average knowledge about COVID-19. Considering the importance of adequate knowledge for proper diagnosis and management of COVID-19, it is suggested to arrange educational programs for dental residents’ knowledge enhancement.